Pengaruh Kemandirian Keuangan Daerah dan Rasio Utang terhadap Financial Sustainability pada Provinsi di Indonesia - Rohmadani, Disma Suci; Yulsiati, Henny; Sari, Yuliana (Politeknik Negeri Ambon, 2024)
This research was designed with the aim of studying the impact of regional financial independence and the debt to financial sustainability ratio on provincial governments in Indonesia. This research uses data from Regional Government Financial Reports (LKPD) for the 2018-2022 period. This type of research is quantitative research. The population of this research is local governments in 34 provinces in Indonesia. The sample used was a saturated sampling technique. The data collection technique used is documentary. The data source uses secondary data. The data analysis method uses multiple regression analysis for panel data. From the research results, it can be concluded that regional financial independence has a positive and significant effect on financial sustainability, while the debt to income ratio has a negative and significant effect on financial sustainability. Simultaneously, regional financial independence and the debt-to-income ratio have a significant impact on financial sustainability in provinces in Indonesia.